O-044 Chinese Society of Reproductive Medicine 2018 annual report on ART. (6th August 2021) - Deng, C
Abstract text: Objective: To analysis the Chinese ART data in 2018 to provide evidence for utilization of various ART. Methods: The data of ART of 263 Reproductive Centers in the mainland of China in 2018 were collected by CSRM ART Data Reporting System. A cross-sectional survey of the use of ART technology was performed. Results: In 2018, the CSRM data reporting system reported 105 610 AID/AIH cycles, 323 938 oocyte retrieval cycles, 147 129 fresh embryo transfer cycles, 254 012 frozen-thawed embryo transfer (FET) cycles, and 204 688 newborn . The patient's age was mainly concentrated in the group <35 years old, accounting for 63.75%. The pregnancy rate and live birth rate of retrieval cycles were 52.49% and 42.23% respectively. The pregnancy rate and live birth rate of FET cycles were 48.71% and 37.68% respectively. Among ART complications, the incidence of moderate to severe OHSS was 1.42%, 0.03% postoperative bleeding, 0.01% postoperative pelvic infection, and 0.04% the other complications. The incidence of birth defects of IVF was 0.87%. Conclusions: This study uses "CSRM data reporting system" data to describe and analyze the current status of ART, basically consistent with the comparison in 2016 and 2017 that most cycles with good outcomes. However, no clear conclusions have been drawn on the changes of PGD/PGS cycle, all-freeze cycle and comprehensive analysis should be conducted by combining with laboratory data. Trial registration number: Study funding: Funding source: